Belajar Sejarah Kolonial melalui Pameran Koleksi Lukisan Jadoel - Suratminto, Lilie (Paradigma: Jurnal Kajian Budaya, 2010)
Pictures or paintings of high-rank officials hanged in government or public offices are not only a recent phenomenon. Francois Valentijn (1724-1726) wrote in his book, Oud en Neuw Oost Indien, the common practice of hanging pictures or paintings of high-rank officials even in the eighteenth century in Indonesia when the East India Company (VOC) had its power over the land. The Fatahillah Historic Museum in Jakarta has kept all the pictures and paintings of the Dutch Indies officials from the time of the East India Company (VOC) to 1942. The curriculum vitae of those persona is a corpus for research on some aspects of the Indonesian colonial history.